Stress Levels Escalate When Repeatedly Performing Tasks Involving Threats - Bertilsson, Johan; Niehorster, Diederick C.; Fredriksson, Peter Jan; Dahl, Mats; Granér, Simon; Fredriksson, Ola; Mårtensson, Johan Magnus; Magnusson, Måns; Fransson, Per-Anders; Nyström, Marcus (Frontiers in Psychology, 2019)
Police work may include performing repeated tasks under the influence of psychological stress, which can affect perceptual, cognitive and motor performance. However, it is largely unknown how repeatedly performing stressful tasks physically affect police officers in terms of heart rate and pupil diameter properties. Psychological stress is commonly assessed by monitoring the changes in these biomarkers. Heart rate and pupil diameter was measured in 12 male police officers when performing a sequence of four stressful tasks, each lasting between 20 and 130 seconds. The participants were first placed in a dimly illuminated anteroom before allowed to enter a brightly lit room where a scenario was played out. After each task was performed, the participants returned to the anteroom for about 30 seconds before performing the next sequential task. Performing a repeated sequence of stressful tasks caused a significant increase in heart rate (p=0.005). The heart rate started to increase already before entering the scenario room and was significantly larger just after starting the task than just before starting the task (p<0.001). This pattern was more marked during the first tasks (p<0.001). Issuance of a verbal ‘abort’ command which terminated the tasks led to a significant increase of heart rate (p=0.002), especially when performing the first tasks (p=0.002). The pupil diameter changed significantly during the repeated tasks during all phases but in a complex pattern where the pupil diameter reached a minimum during task 2 followed by an increase during tasks 3 and 4 (p≤0.020). During the initial tasks, the pupil size (p=0.014) increased significantly. The results suggest that being repeatedly exposed to stressful tasks can produce in itself an escalation of psychological stress, this even prior to being exposed to the task. However, the characteristics of both the heart rate and pupil diameter were complex, thus, the findings highlight the importance of studying the effects and dynamics of different stress-generating factors. Monitoring heart rate was found a useful method to screen police officers for stress responses, and thus, to get an indication if and when rotation of deployed personnel is necessary, avoiding sustained high stress exposures by allowing de-escalating rests.